2021
DOI: 10.3892/etm.2021.10181
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of serum α‑fetoprotein in viral hepatitis C without hepatocellular carcinoma

Abstract: Viral hepatitis C represents a significant liver pathology worldwide, with a detrimental impact on national health systems. The present study aimed to correlate the levels of serum α-fetoprotein (AFP) with prognostic tools such as Fibroscan ® , the presence of mixed cryoglobulinemia, and various demographic and standard biochemical markers, in patients with chronic hepatitis C, unrelated to hepatocellular carcinoma (HCC). A clinical study was designed considering three study groups: Hepatitis C virus (HCV) gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The importance of HCV cure in hemodialysis patients has two dimensions: Avoidance of progression of liver disease and its complications on the one hand, and ensuring optimal conditions for a potential kidney transplant on the other (8). A recent study evaluated the impact of HCV on liver inflammation by demonstrating increased alpha-fetoprotein levels in HCV-infected patients in the absence of hepatocellular carcinoma (21). Regarding alpha-fetoprotein in dialysis patients, it has been shown that levels do not increase with uremia but in fact decrease after dialysis sessions, thus raising questions of interpretation regarding its value as a tumor marker in patients with end-stage kidney disease (22).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of HCV cure in hemodialysis patients has two dimensions: Avoidance of progression of liver disease and its complications on the one hand, and ensuring optimal conditions for a potential kidney transplant on the other (8). A recent study evaluated the impact of HCV on liver inflammation by demonstrating increased alpha-fetoprotein levels in HCV-infected patients in the absence of hepatocellular carcinoma (21). Regarding alpha-fetoprotein in dialysis patients, it has been shown that levels do not increase with uremia but in fact decrease after dialysis sessions, thus raising questions of interpretation regarding its value as a tumor marker in patients with end-stage kidney disease (22).…”
Section: Discussionmentioning
confidence: 99%
“…For clinical purposes, West Haven criteria are used to classify HE into four stages, but they are often used subjectively and fail to accurately identify minimal hepatic encephalopathy (mHE). Thus, further efforts should be made to identify novel predictive biomarkers in various subclinical cirrhosis-associated conditions that could lead to cognitive impairment [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the screening tests and therapeutic algorithms are well-established in various hepatic diseases, including liver transplantation as etiologic therapy in end-stage liver disease, strategies to identify reversible lesions in early stages and to develop new epigenetic therapies should be prioritized ( 18-20 ).…”
Section: Introductionmentioning
confidence: 99%